2017
DOI: 10.2174/1874357901711010073
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immune Responses in Pigs Infected with Chinese Highly Pathogenic PRRS Virus Strain HV and North American Strain NADC-20

Abstract: Introduction:Chinese HP-PRRSV characterized by high morbidity and mortality of all ages of pigs emerged since 2006 in China. The immune response of HP-PRRSV was never compared with conventional low pathogenic PRRSV strain. Objective:In this study, we compared the immune responses elicited by a Chinese HP-PRRSV strain HV and a North American RRSV strain NADC20 infections. Result:Pigs infected with NADC-20 showed significantly higher Ab titers than HV-PRRSV infected pigs at 9 DPI. Infection with HV-PRRSV induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In our study, IDO1 was highly up-regulated at 6 dpi in both infected groups but mainly in virulent Lena-infected pigs, coinciding with a peak of IFN-g concentration in serum, as previously reported in a parallel study (52). An increase in TNFa serum concentration has been also observed in the early phase of infection by Lena strain (53) as well as by other virulent PRRSV strains (54,55). Interestingly, other immune checkpoints, such as PD-1/PD-L1, CTLA-4 and CD200R1, are associated with IDO-1 expression (49, 50), which is supported in our study by the correlation observed between CTLA4 and IDO1 (r = 0.78), between PD1 and IDO1 (r = 0.54) and between PDL1 and IDO1 (r = 0.65) in the thymus from virulent Lenainfected group.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, IDO1 was highly up-regulated at 6 dpi in both infected groups but mainly in virulent Lena-infected pigs, coinciding with a peak of IFN-g concentration in serum, as previously reported in a parallel study (52). An increase in TNFa serum concentration has been also observed in the early phase of infection by Lena strain (53) as well as by other virulent PRRSV strains (54,55). Interestingly, other immune checkpoints, such as PD-1/PD-L1, CTLA-4 and CD200R1, are associated with IDO-1 expression (49, 50), which is supported in our study by the correlation observed between CTLA4 and IDO1 (r = 0.78), between PD1 and IDO1 (r = 0.54) and between PDL1 and IDO1 (r = 0.65) in the thymus from virulent Lenainfected group.…”
Section: Discussionsupporting
confidence: 90%
“…Some parameters seem to correlate with the PRRSV virulence phenotype. For example, high fever, anorexia, and lethargy are generally observed in pigs infected with virulent PRRSV strains [20,[53][54][55][56][57][58][59]. Viremia levels have been reported to be higher for infections with virulent PRRSV-1 isolates or PRRSV-2 isolates [53,59,60]; however, the PRRSV-1 isolate SU1-bel induced lower and shorter viremia in comparison with the reference Lelystad isolate, although SU1-bel isolate caused a greater clinical score and gross lung lesions [61].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study suggests that there is a negative correlation between high body temperature and the survival time for HP-PRRSV-infected piglets ( 5 ). And high fever is also related to virulence ( 38 ). Thus, it is necessary to explore the mechanisms on how HP-PRRSV triggers high fever in pigs.…”
Section: Discussionmentioning
confidence: 99%